Modern PHP Web Development with MySQL, GitHub and Heroku - Williams, Trevoir (Packt Publishing, 2020)
Unlock powerful techniques to develop and deploy data-driven web applications using PHP, MySQL, Heroku, and learn how to manage them with GitHub. About This Video Discover the role of PHP in web-based applications Learn how to use XAMPP to set up PHP environment, MySQL Database, and Apache Server Unlock techniques to manage a PHP application with GitHub In Detail With PHP, you can easily develop a robust web application in no time. Even non-programmers and beginners find PHP a great tool to get started with web development. This course will take you through the process of building an amazing web application in PHP. The course starts with an introduction to PHP and then takes you through the learning objectives. Next, you will learn to set up a PHP environment using XAMPP and install Visual Studio Code on your machines. In addition to this, you will also learn to install the Composer package manager and create a GitHub and Heroku account. Next, you will discover how PHP works and understand its basics and syntaxes on the go. Moving along, you will go through the process of building a PHP website and learn the steps for publishing a website to Heroku. Finally, you will learn to create and manage databases with phpMyAdmin and MySQL Workbench. By the end of this course, you will be well-versed with PHP and will have developed the essential skills needed to build a data-driven web application.